Android application development all-in-one for dummies - Burd, Barry (New Delhi Wiley, 2017)
Android is everywhere, and Burd shows you how to get your piece of the action. This all-in-one guide to creating great apps for this booming market takes you from groundwork through the essentials common to every app, to actually marketing your apps and learning advanced techniques involving C and C++.
Introduction -- Getting started with Android application development -- Android background material --The building blocks -- Programming cool phone features -- Apps for tablets, watches, and TV sets -- The job isn't done until....
"6 books in 1" -- Cover
Includes index.
Keywords: Application software -- Development; Mobile computing; Computer software -- Development; Smartphones -- Programming; Android (Electronic resource)